Uncertainty shocks and financial crisis indicators - Nikolay Hristov; Markus Roth (Deutsche Bundesbank, 2019)
The current paper broadens the understanding for the role of uncertainty in the context of a macroeconomic environment. It focuses on the implications of uncertainty shocks on indicators that tend to precede financial crises. In an empirical analysis we show for a set of four euro area countries that negative uncertainty shocks, while accompanied by favorable effects to economic activity, are followed by unfavorable reactions of financial crisis indicators. We conclude that uncertainty indicators contain some useful information on the potential buildup of vulnerabilities in the financial system.
Keywords: D89; C32; E44; G01; 330; uncertainty; crisis indicators; structural macroeconomic shocks; signrestrictions